Management Control Systems in Small and Medium-Sized Enterprises: A Case Study (International Journal of Scientific Research and Management (IJSRM), 2022)
Small and medium-sized enterprises (SMEs) are the pillar of the Philippine economy. They comprise 99.6% of the total business establishments in the market. Many studies have said that SMEs, particularly small enterprises, do not utilize management control systems (MCS) due to their simple organizational structure and limited resources. Only a few studies have indicated that these firms have established and are using MCS even those sophisticated management accounting practices (MAPs) and information. This empirical study was conducted to get an understanding of the use and the form of MCSs applied in SMEs in Misamis Occidental and to explore on their implementation of control. The study used the case study method. The study included 46 SMEs surveyed and seven SMEs interviewed. The companies have already been in the industry for more than 10 years and employed from 10 to 199 persons. They are a combination of traditional and modern enterprises due to the generation of the owners/managers handling the business operations. The results suggest that SMEs in Misamis Occidental do use a wide range of MCS practices and information although many practices are not integrated as highly and systematically into their normal operations based on the data of adoption rates and ranks. The results also indicate that MCS are themed along the lines of financial controls, clan controls, customer-oriented controls, relationship controls, and strategic-oriented controls. This shows a combination of traditional MCS and new sophisticated MCS which adds to the knowledge that SMEs do practice and adopt MCS in their operations.